Active Rho is localized to podosomes induced by oncogenic Src and is required for their assembly and function - Berdeaux, Rebecca L. (The Rockefeller University Press, 2004)
Transformation of fibroblasts by oncogenic Src causes disruption of actin stress fibers and formation of invasive adhesions called podosomes. Because the small GTPase Rho stimulates stress fiber formation, Rho inactivation by Src has been thought to be necessary for stress fiber disruption. However, we show here that Rho[GTP] levels do not decrease after transformation by activated Src. Inactivation of Rho in Src-transformed fibroblasts by dominant negative RhoA or the Rho-specific inhibitor C3 exoenzyme disrupted podosome structure as judged by localization of podosome components F-actin, cortactin, and Fish. Inhibition of Rho strongly inhibited Src-induced proteolytic degradation of the extracellular matrix. Furthermore, development of an in situ Rho[GTP] affinity assay allowed us to detect endogenous Rho[GTP] at podosomes, where it colocalized with F-actin, cortactin, and Fish. Therefore, Rho is not globally inactivated in Src-transformed fibroblasts, but is necessary for the assembly and function of structures implicated in tumor cell invasion.